Study on the Loading-unloading Hysteresis of an AFM Tip with a Surface of Soft Materials Master thesis - Batkhuu B.; (NmONGOL uLSYN iH sURGUULXs (UB., 2012)
(NaNGLI H\Ls
(NdIP(B-3830s
Keywords: (NHIMIs; (NFIZIK HIMIs; (NMATERIALYN GADARGUUs